Automatic Feature Recognition Using the Medial Axis for Structured Meshing of Automotive Body Panels. (July 2020) - Makem, Jonathan E.; Fogg, Harold J.; Mukherjee, Nilanjan
Abstract: As a feature sensitive meshing investigation, this paper focuses on the identification and meshing of four categories of features specific to automotive body panels, namely beads, fillets, flanges and tabs . An improvised and enhanced medial axis based strategy is proposed for identifying the aforementioned features. Appropriate boundary discretisation, inclusion of zero medial vertex case for annulus identification, medial axis topology modifications to eliminate undesirable pathologies, T-junction squaring with cubic filtering smoothing highlight some of the improvisations to the medial axis technology employed. Ridge curves representing the crest lines of beads and fillets are extracted and inserted on the face. A combination of multi-blocking, clamping and face node-loop insertion, followed by boundary connection strategies are used to generate high fidelity, feature sensitive, quasi-structured meshes. Graphical abstract: Highlights: Strategies for identifying, processing and meshing features are presented. Cubic smoothing and T-junction squaring improve medial egde geometry. Bead, flange, tab and fillet features are identified and processed. Feature-specific multiblocking facilitates structured meshes honouring crest lines. Narrow fillets are identified and abstracted to form ridge edges.